SOSIALISASI PRODUK PERBANKAN SYARIAH DAN PASAR MODAL SYARIAH SEBAGAI INSTRUMEN INVESTASI AMAN BAGI GENERASI MILENIAL YAYASAN AHYA BILKHAIR (PENDEKATAN PAR) - Indra Marzuki (DEVELOPMENT: Journal of Community Engagement, 2025)
The millennial generation currently lives amidst a massive digitalization of financial information. Unfortunately, their high desire for financial independence often leads to the trap of illegal/fake investments due to low literacy regarding safe and sharia-compliant investment instruments. This community service project aims to socialize and assist 85 millennials in the Ahya Bilkhair Foundation environment, Serua, Ciputat, South Tangerang City, enabling them to utilize Sharia Banking and Sharia Capital Market products as safe, legal, and halal investment instruments. Utilizing the Participatory Action Research (PAR) method, this project actively engaged participants in cycles of financial portfolio mapping, critical reflection on the Fear of Missing Out (FOMO) phenomenon, planning, account opening simulation, and evaluation. Initial observations indicated that participants' literacy regarding instruments such as Sukuk, Sharia Mutual Funds, and the Sharia Online Trading System (SOTS) was very low, as they were more familiar with speculative applications. Through participatory actions such as dissecting sharia financial applications and opening sharia securities accounts, the participants' understanding and financial risk mitigation skills increased significantly from an average of 43 to 88. The conclusion of this activity affirms that applicative sharia financial literacy education can transform the millennial generation at the Ahya Bilkhair Foundation from objects of speculative investment exploitation into smart investors who contribute to strengthening the Islamic economic ecosystem.